Reliability of OperaVOX against Multidimensional Voice Program (MDVP). (February 2015) - Mat Baki, M.; Wood, G.; Alston, M.; Ratcliffe, P.; Sandhu, G.; Rubin, J.S.; Birchall, M.A.
<x xml:space="preserve">Abstract</x> Objective To evaluate the agreement between OperaVOX and MDVP. Design Cross sectional reliability study. Setting University teaching hospital. Methods Fifty healthy volunteers and 50 voice disorder patients had supervised recordings in a quiet room using OperaVOX by the iPod's internal microphone with sampling rate of 45 kHz. A five‐seconds recording of vowel/a/was used to measure fundamental frequency (F0), jitter, shimmer and noise‐to‐harmonic ratio (NHR). All healthy volunteers and 21 patients had a second recording. The recorded voices were also analysed using the MDVP. The inter‐ and intrasoftware reliability was analysed using intraclass correlation (ICC) test and Bland–Altman (BA) method. Mann–Whitney test was used to compare the acoustic parameters between healthy volunteers and patients. Results Nine of 50 patients had severe aperiodic voice. The ICC was high with a confidence interval of >0.75 for the inter‐ and intrasoftware reliability except for the NHR. For the intersoftware BA analysis, excluding the severe aperiodic voice data sets, the bias (95% LOA) of F0, jitter, shimmer and NHR was 0.81 (11.32, −9.71); −0.13 (1.26, −1.52); −0.52 (1.68, −2.72); and 0.08 (0.27, −0.10). For the intrasoftware reliability, it was −1.48 (18.43, −21.39); 0.05 (1.31, −1.21); −0.01 (2.87, −2.89); and 0.005 (0.20, −0.18), respectively. Normative data from the healthy volunteers were obtained. There was a significant difference in all acoustic parameters between volunteers and patients measured by the Opera‐VOX (P < 0.001) except for F0 in females (P = 0.87). Conclusion OperaVOX is comparable to MDVP and has high internal consistency for measuring the F0, jitter and shimmer of voice except for the NHR.